2018
DOI: 10.1039/c8ob01280f
|View full text |Cite
|
Sign up to set email alerts
|

Tsavoenones A–C: unprecedented polyketides with a 1,7-dioxadispiro[4.0.4.4]tetradecane core from the lichen Parmotrema tsavoense

Abstract: New racemic dispiranic polyketides, tsavoenones A (1), B (2) and C (3), having a novel 1,7-dioxadispiro[4.0.4.4]tetradecane scaffold were isolated from the foliose lichen Parmotrema tsavoense. These compounds were structurally elucidated by extensive NMR analyses, comparison between experimental and theoretical 13C NMR data and X-ray crystallography. A putative biosynthetic scenario for the formation of 1-3 from parmosidone D, a meta-depsidone previously isolated from the same lichen material, was proposed. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Even though some recent genetic studies delineated alternative biosynthetic scenarios proceeding from anthraquinone precursors [38], it was long inferred that diphenylethers arise by catabolism of their congeneric depsidones [39], thereby giving support to the C-1 location of a methyl ester moiety, which cannot be straightforwardly located based on spectroscopic features. Similar biochemical events were also proposed to step in the biosynthesis of the structurally unique tsavoenones [20].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Even though some recent genetic studies delineated alternative biosynthetic scenarios proceeding from anthraquinone precursors [38], it was long inferred that diphenylethers arise by catabolism of their congeneric depsidones [39], thereby giving support to the C-1 location of a methyl ester moiety, which cannot be straightforwardly located based on spectroscopic features. Similar biochemical events were also proposed to step in the biosynthesis of the structurally unique tsavoenones [20].…”
Section: Resultsmentioning
confidence: 62%
“…As of 2020, lichens are still deemed to constitute a largely untapped source of bioactive specialized metabolites [17]. Our recent phytochemical investigations shed light on the wealth of the chemical diversity sheltered by Vietnamese lichen species [18], which sometimes comprised unprecedented scaffolds [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Isostructural depsidone/diphenylether pairs are of considerable generality in lichens since the latter can be obtained by simple hydrolysis of the former [18]. At last, the unprecedented dioxadispiro[4.0.4.4]tetradecane scaffold of tsavoenones A-C was proposed to derive from parmosidone D, based on a biosynthetic scenario that was partly reminiscent of griseofulvin biosynthesis [7]. To the best of our knowledge, parmosidone H (3) represents the first report of a 2H-chromen-bearing depsidone in lichen.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that lichen metabolites possess potent α-glucosidase inhibitory activity [3][4][5]. In previous studies on the Vietnamese lichen Parmotrema tsavoense, we described several novel depsidones and diphenyl ethers [6][7][8]. However, there has been no investigation on the presence of α-glucosidase inhibitors in this lichen.…”
Section: Introductionmentioning
confidence: 95%
“…Four highly oxygenated p-terphenyl derivatives, including hawaiienol A 6, have been identified as metabolites of the insect-associated fungus Paraconiothyrium hawaiiense. 6 Hawaiienol A 6 is the first example of a terphenyl with a 4,7dioxatricyclo[3.2.1.0 3,6 ]octane unit and its structure and absolute configuration were determined by X-ray analysis. Further unusual natural products whose structures have been confirmed by X-ray analyses include cleistoperlones A 7 and C 8, from Cleistocalyx operculatus, 7 and eucalyptusdimer A 9, from Eucalyptus robusta.…”
mentioning
confidence: 99%